Measurement of the cross-section ratio [sigma] ([chi]c2)/[sigma]([chi]c1) for prompt χc production at √s=7 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; et al. (Physics letters, 2012)
The prompt production of the charmonium χc1 and χc2 mesons has been studied in proton-proton collisions at the Large Hadron Collider at a centre-of-mass energy of s=7 TeV. The χc mesons are identified through their decays χc→J/ψγ with J/ψ→μ+μ− using 36 pb−1 of data collected by the LHCb detector in 2010. The ratio of the prompt production cross-sections for the two χc spin states, σ(χc2)/σ(χc1), has been determined as a function of the J/ψ transverse momentum, pTJ/ψ, in the range from 2 to 15 GeV/c. The results are in agreement with the next-to-leading order non-relativistic QCD model at high pTJ/ψ and lie consistently above the pure leading-order colour-singlet prediction.
Im Titel sind "sigma" und "chi" als griechische Buchstaben dargestellt
Gesehen am 13.07.2018